2017
DOI: 10.3847/1538-3881/aa94cf
|View full text |Cite
|
Sign up to set email alerts
|

The Broadband and Spectrally Resolved H-band Eclipse of KELT-1b and the Role of Surface Gravity in Stratospheric Inversions in Hot Jupiters

Abstract: We present a high precision H-band emission spectrum of the transiting brown dwarf KELT-1b, which we spectrophotometrically observed during a single secondary eclipse using the LUCI1 multiobject spectrograph on the Large Binocular Telescope. Using a Gaussian-process regression model, we are able to clearly measure the broadband eclipse depth as ∆H = 1418 ± 94 ppm. We are also able to spectrally-resolve the H-band into five separate wavechannels and measure the eclipse spectrum of KELT-1b at R ≈ 50 with an aver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 42 publications
3
68
2
Order By: Relevance
“…Kelt-1b, orbiting a 6500 K F5V star lacks the intense UV irradiation of the white dwarf irradiated systems, and does not show this brightening. Indeed eclipse measurements suggest that this object fits very well with a field dwarf template (Croll et al 2015;Beatty et al 2017).…”
Section: Discussionmentioning
confidence: 54%
“…Kelt-1b, orbiting a 6500 K F5V star lacks the intense UV irradiation of the white dwarf irradiated systems, and does not show this brightening. Indeed eclipse measurements suggest that this object fits very well with a field dwarf template (Croll et al 2015;Beatty et al 2017).…”
Section: Discussionmentioning
confidence: 54%
“…It is possible that Kepler-13-Ab's dayside temperature profile does become inverted at lower pressure levels than probed by the observations, but our inference that Kepler-13Ab's dayside temperature is monotonically decreasing is further supported by the fact that the shape and amplitude of our HST/WFC3 spectrum show that the dayside of Kepler-13Ab appears similar to the spectrum of a field M7 dwarf. We contend that the dual facts that Kepler-13Ab possesses a decreasing temperature-pressure profile and a relatively high surface gravity support the hypothesis of Beatty et al (2016) that both surface gravity and temperature play a role in determining the presence of a stratospheric temperature inversion in hot Jupiters. Specifically, in high-surface-gravity planets such as Kepler-13Ab, the characteristic freefall time within the atmosphere is substantially shorter (Equation (11)).…”
Section: Discussionmentioning
confidence: 86%
“…Recent observations of KELT-1b's emission spectrum by Beatty et al (2016), which has a dayside temperature of 3150 K and a surface gravity 22 times Jupiter's, showed a noninverted, monotonically decreasing temperature profile, which led those authors to suggest that surface gravity also plays a strong role in setting the vertical temperature of hot Jupiters. The similar dayside temperature, but lower surface gravity, of Kepler-13Ab therefore presented itself as a relevant comparison object.…”
Section: Introductionmentioning
confidence: 99%
“…The broadband thermal emission from KELT-1b has previously been observed by Spitzer at 3.6 µm and 4.5 µm Beatty et al (2014) K (Croll et al 2015, and z (Siverd et al 2012) eclipses. Beatty et al (2017b) also observed an R ≈ 50 H-band eclipse spectrum.…”
Section: Introductionmentioning
confidence: 84%